2007
DOI: 10.2355/isijinternational.47.472
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Conditions of the Chromium Nitride Formation in a ULC Steel of Fe-Cr-N Type with 0.7% Cr

Abstract: Fig. 4. Evolution of D(DS a ) as a function of the ageing time at 120°C for the investigated steel treated for: (a) 1 min at T H ϩ24 h at 270°C or (b) 15 min at T H ϩ24 h at 270°C, cold-rolled (eϾ80 %) and then aged for different times at 120°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…31) The precipitate was found to be γ-CrN with a cubic structure of a = 0.414 nm, as was previously reported by Massardier et al 32) Our internal friction measurement has shown that, as presented in Fig. 7, the precipitation nose of CrN was around 650-700°C, and the amount of CrN increased with increasing Cr content.…”
Section: Precipitation Kinetics Of Cr Nitridesupporting
confidence: 80%
See 1 more Smart Citation
“…31) The precipitate was found to be γ-CrN with a cubic structure of a = 0.414 nm, as was previously reported by Massardier et al 32) Our internal friction measurement has shown that, as presented in Fig. 7, the precipitation nose of CrN was around 650-700°C, and the amount of CrN increased with increasing Cr content.…”
Section: Precipitation Kinetics Of Cr Nitridesupporting
confidence: 80%
“…As the better dent resistance is obtained by the higher yield stress after paint baking, higher yield strength after forming and subsequent baking process is preferred. However, the amount of yield strength increase during baking at 170°C for 1.2 ks after 2% prestraining, which is a typical measure of BH, is limited to [30][31][32][33][34][35][36][37][38][39][40] MPa. This is because anti-aging property at room temperature deteriorates with increasing the amount of BH.…”
Section: Introductionmentioning
confidence: 99%